Light Intensity Modulates the Response of Two Antarctic Diatom Species to Ocean Acidification - Heiden, Jasmin P.; Bischof, Kai; Trimborn, Scarlett (Frontiers in Marine Science, 2016)
It is largely unknown how rising atmospheric CO2 concentrations and changes in the upper mixed layer depth, with its subsequent effects on light availability will affect phytoplankton physiology in the Southern Ocean. Linking seasonal variations in the availability of CO2 and light to abundances and physiological traits of key phytoplankton species could aid to understand their abilities to acclimate to predicted future climatic conditions. To investigate the combined effects of CO2 and light on two ecologically relevant Antarctic diatoms (Fragilariopsis curta and Odontella weisflogii) a matrix of three light intensities (LL = 20, ML = 200, HL = 500 μmol photons m−2 s−1) and three pCO2 levels (low = 180, ambient = 380, high = 1000 μatm) was applied assessing their effects on growth, particulate organic carbon (POC) fixation and photophysiology. Under ambient pCO2, POC production rates were highest already at low light in Fragilariopsis, indicating saturation of photosynthesis, while in Odontella highest rates were only reached at medium irradiances. In both species ocean acidification did not stimulate, but rather inhibited, growth and POC production under low and medium light. This effect was, however, amended under high growth irradiances. Low pCO2 levels inhibited growth and POC production in both species at low and medium light, and further decreased absolute electron transport rates under high light. Our results suggest that Southern Ocean diatoms were sensitive to changes in pCO2, showing species-specific responses, which were further modulated by light intensity. The two diatom species represent distinct ecotypes and revealed discrete physiological traits that matched their seasonal occurrence with the related physical conditions in Antarctic coastal waters.